Night of the living dummy III - Stine, R. L. (New York : Scholastic, 1996)
Trina's dad used to be a ventriloquist but now his dummies are in the attic. Trina and her brother Dan hear voices in the attic, could the dummies be alive?
"An Apple paperback."
"Parachute Press book"--T.p. verso.
450
Accelerated Reader AR
Keywords: Horror stories; Venriloquism -- Fiction; Puppets -- Fiction